Exhibition texts of statue collection in the museum: Translation method and techniques revisited - Muhammad Zainal Muttaqien; Kurniawan Kurniawan; Zainal 'Arifin; Selma Mutia Rani (Universitas Islam Sultan Agung, 2026)
For the purpose of informing and attracting foreign visitors, the exhibition texts of the objects exhibited in local museums are commonly completed with their translations in English. However, mistakes are often found in the translated versions of exhibition texts due to the unavailability of local and cultural term equivalents in the target language, as well as inappropriateness in the translation procedure. This descriptive-qualitative research aims at finding out the ways the exhibition texts of the statue collection in a local museum were translated from Indonesian to English, as well as identifying the mistakes made by the translators. The data were collected from Radya Pustaka Museum in Surakarta using a documentation technique. These data were then analyzed by applying the theories of translation methods from Newmark (1988) and translation techniques from Molina and Albir (2002) through Miles & Huberman’s (1994) interactive model of analysis. For validating the data, an investigator triangulation was conducted by involving three experts in linguistics. The findings show that, in dealing with the method, the translator employed literal translation. It is evident from the equivalence of words and the sameness of the sentence structures between the source and target texts. Regarding the techniques, 8 out 18 translation techniques were applied, namely: borrowing, reduction, transposition, amplification, literal translation, generalization, particularization, and modulation. To complete this study, it is necessary to make an assessment to measure the translation quality of the exhibition text translation in the future.